Single-cell RNA sequencing reveals cell type-specific immune regulation associated with human neuromyelitis optica spectrum disorder - Jiang, Yushu; Dai, Shuhua; Pang, Rui; Qin, Lingzhi; Zhang, Milan; Liu, Huiqin; Wang, Xiaojuan; Zhang, Jiewen; Peng, Gongxin; Wang, Yongchao; Li, Wei (Frontiers in Immunology, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune disease.However, the peripheral immune characteristics of NMOSD remain unclear. Here, peripheral blood mononuclear cells from patients with NMOSD are characterized using single-cell RNA sequencing (scRNA-seq). The differentiation and activation of lymphocytes, expansion of myeloid cells, and an excessive inflammatory response in innate immunity are observed. Flow cytometry analyses confirm a significant increase in the percentage of plasma cells among B cells in NMOSD. NMOSD patients exhibit 2 an elevated percentage of CD8+ T cells within the T cell population. Oligoclonal expansions of B cell receptors are observed after therapy. Additionally, NMOSD patients show higher expression levels of CXCL8, IL7, IL18, TNFSF13, IFNG, and NLRP3. High-dimensional single-cell profiling of both innate and adaptive immune responses reveals disease-specific immune cell subsets and identifies potential new targets for NMOSD.